The Secretome Derived From Mesenchymal Stromal Cells Cultured in a Xeno-Free Medium Promotes Human Cartilage Recovery in vitro - Palamà, Maria Elisabetta Federica; Shaw, Georgina Margaret; Carluccio, Simonetta; Reverberi, Daniele; Sercia, Laura; Persano, Luana; Pisignano, Dario; Cortese, Katia; Barry, Francis Peter; Murphy, Josephine Mary; Gentili, Chiara (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoarthritis (OA) is a disabling joint disorder causing articular cartilage degeneration. Currently, the treatments are mainly aimed to pain and symptoms relief, rather than disease ameliorate. Human bone marrow stromal cells (hBMSCs) have emerged as a promising paracrine mechanism-based tool for the OA treatment. Here, we investigate the therapeutic potential of conditioned media (CM) and extracellular vesicles (EVs) isolated from hBMSCs grown in a xeno-free culture system (XFS) compared to the conventional fetal bovine serum-culture system (FBS) in an in vitro model of OA. First, we observed that XFS promoted growth and viability of hBMSCs compared to FBS-containing medium while preserving their typical phenotype. The biological effects of the CM derived from hBMSC cultivated in XFS- and FBS-based medium were tested on IL-1α treated human chondrocytes, to mimic OA environment. Treatment with CM derived from XFS-cultured hBMSC inhibited IL-1α-induced expression of IL-6, IL-8 and COX-2 by hACs compared to FBS-based condition. Furthermore, we observed that hBMSCs grown in XFS produced a higher amount of EVs compared to FBS-culture. The hBMSC-EVs not only inhibit the adverse effects of IL-1α-induced inflammation, but play a significant at least in vitro chondroprotective effect. In conclusion, the XFS medium was found to be suitable for isolation and expansion of hBMSCs with increased safety profile and intended for ready-to-use clinical therapies.